Portable glossaries: a to-go terminological tool for public service interpreters in training - Monguilod Navarro, Laura; Antequera Manzano, Sofía (Estudios de Traducción, 2026)
Despite being a highly necessary discipline to ensure migratory rights, public service interpreting and translation (PSIT) is still an undeveloped profession in many countries. The following research arises as a way to increase training and professionalisation efforts for the job by determining the applicability of informational resources addressed for migrants as linguistic resources for language provision. Within this context, we propose the creation of what we call portable glossaries, which are concise terminological glossaries (10-15 terms of each grammatical category) that include the most important or problematic terminology on a specific area and can be carried around during the interpreting job. To create these glossaries, a corpus analysis has been performed on a total of 69 open-access, official resources addressed at interpreters and migrants, to ensure the actual relevance of the chosen terminology. These glossaries focus on the areas of legal, humanitarian and medical terminology, as well as acronyms, but may be upgraded if analysis of further resources is performed. With this proposal, we expect to facilitate resources for interpreters in training, native speakers that find themselves acting as ad hoc interpreters, as well as public services providers in need, in an attempt to improve public service accessibility and quality for migrants.